STUDI EKSPERIMEN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION) PADA MATERI EKOSISTEM - Purba, Ika Rosenta (Program Studi Pendidikan Biologi, 2020)
This study aims to determine student learning outcomes using the cooperative learning model type TAI (Team Assisted Individualization) on ecosystem material in SMA Negeri 6 Pematangsiantar. This research was conducted on February-March 2019 in class X (1st) SMA Negeri 6 Pematangsiantar. The population in this study was class X SMA Negeri 6 Pematangsiantar with 9 classes. The sampling method is Cluster Random Sampling, and get class X-1 as an experimental class and class X-5 as a control. The results of the analysis of the mean value of the pre-test of the control class = 38.38, the experimental class = 52.66 and the average value of the post-test of the control class = 59.75, the experimental class = 79.66. The results of the standard deviation analysis of the control class pretest = 13,886, the experimental class = 9,468 and the posttest standard deviation of the control class = 14,458, the experimental class = 6,454. The results of the hypothesis analysis (t test) were obtained t-count = 6.985 and t-table =1.99. Based on the results of research and analysis it can be concluded that the cooperative learning model of the TAI (Team Assisted Individualization) type is better for improving learning outcomes compared to conventional learning on ecosystem material in class X SMA Negeri 6 Pematangsiantar